JENIS-JENIS IKAN YANG TERTANGKAP DI BATANG AIR DINGIN KELURAHAN BALAI GADANG KECAMATAN KOTO TANGAH KOTA PADANG (Universitas PGRI Sumatera Barat, 2012)
ABSTRACTCutting woods on the upstream is the main cause of forest damage. Thisactivity is done continuously by the people for firewood and timber. The area thathas damaged is not only at the upstream but also at the buffer zone of Batang AirDingin River. The damage affects the population of various fish in this area.Concerning this condition, the research was conducted to find out the species offish in Batang Air Dingin river on January to March 2012. The instruments whichare use to catch the fish are net, gill net, disperse net, shock fishing andaccumulator and the sampling technique was purposive sampling. Sampleidentification was conducted in Biology laboratory of STKIP PGRI WestSumatera. The sampling technique was purposive sampling. The research foundthat from 544 fishes, there are 19 species which are classified into 10 families.